2015
DOI: 10.18632/oncotarget.3660
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12-induced VLA-4 activation is impaired in trisomy 12 chronic lymphocytic leukemia cells: a role for CCL21

Abstract: Homing to distinct lymphoid organs enables chronic lymphocytic leukemia (CLL) cells to receive pro-survival and proliferative signals. Cytogenetic aberrations can significantly affect CLL cell compartmentalization. Trisomy 12 (tri12) defines a CLL subgroup with specific clinical features and increased levels of the negative prognostic marker CD49d, the α4-subunit of the integrin VLA-4, which is a key regulator of CLL cell homing to bone marrow (BM). Chemokine-induced inside-out VLA-4 activation, particularly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 49 publications
5
35
0
Order By: Relevance
“…Both OSU-CLL cell lines expressed high levels of CCR7 and low levels of CXCR4 ( Fig. 1B), which is in line with chemokine receptor expression profiles found in trisomy 12-positive CLL cells (14). Control experiments revealed that primary human PBLs and mature monocyte-derived dendritic cells express similar mRNA levels of CCR7 but lower levels of CXCR4 compared with the OSU-CLL cell lines (Supplemental Fig.…”
Section: Enhanced Migration Of Zap70-positive Cll Cells Toward Ccr7 Asupporting
confidence: 81%
See 2 more Smart Citations
“…Both OSU-CLL cell lines expressed high levels of CCR7 and low levels of CXCR4 ( Fig. 1B), which is in line with chemokine receptor expression profiles found in trisomy 12-positive CLL cells (14). Control experiments revealed that primary human PBLs and mature monocyte-derived dendritic cells express similar mRNA levels of CCR7 but lower levels of CXCR4 compared with the OSU-CLL cell lines (Supplemental Fig.…”
Section: Enhanced Migration Of Zap70-positive Cll Cells Toward Ccr7 Asupporting
confidence: 81%
“…Trisomy 12-positive CLL cells display higher rates of cell proliferation (13) and lymph node involvement (14,15), and consequently patients carrying trisomy 12 CLL cells are susceptible to a fast disease progression (16). Moreover, trisomy 12 CLL cells are described to express high levels of the integrins very late antigen ABBREVIATIONS: BCR, B-cell receptor; BSA, bovine serum albumin; CD, cluster of differentiation; CLL, chronic lymphocytic leukemia; HEV, high endothelial venule; huICAM, human intercellular adhesion molecule; huVCAM, human vascular cell adhesion molecule; ICAM, intercellular adhesion molecule; IgV H , immunoglobulin heavy chain variable region; LFA-1, lymphocyte function-associated antigen; OSU, Ohio State University; PBL, peripheral blood lymphocyte; pMBMEC, primary mouse brain microvascular endothelial cell; VCAM, vascular cell adhesion molecule; VLA, very late antigen; ZAP70, z-associated protein of 70 kDa (VLA)-4 and lymphocyte function-associated antigen (LFA)-1, which facilitate integrin-mediated cell adhesion and motility (11,12,14,17). Cluster of differentiation (CD)49d, the a-chain of VLA-4, is considered a negative prognostic marker in CLL (18), particularly for trisomy 12-positive CLL (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 We investigated whether CXCR3 and CXCR4 functionally influence each other in CLL. Performing chemotaxis assays as previously described, 8 we found that CLL cells pre-stimulated with either CXCR3 ligand CXCL9, CXCL10, or CXCL11 exhibited significantly reduced directed cell migration towards CXCL12 ( Figure 2Ai). Pre-stimulation with a small-molecule high-affinity CXCR3 agonist (VUF11418) 9 confirmed this observation and an antagonist (VUF11211) 9 did not interfere with chemotactic ability (Figure 2Aii).…”
supporting
confidence: 55%
“…(B) Shear flow assays were performed as previously described. 8 CLL cells were pretreated with (i) CXCL11 or (ii) the CXCR3 agonist and antagonist where indicated and perfused for 1 min at 0.5 dyn/cm 2 over VCAM-1 co-immobilized with CXCL12. Categories of interactions (tethers) are expressed as frequencies of cells in direct contact with the substrate.…”
mentioning
confidence: 99%